Collective or individual titles? Conflict over tenure regularisation in a Kenyan informal settlement. (October 2016) - Rigon, Andrea
Providing formal titles to residents in densely populated informal settlements without fuelling conflict or encouraging gentrification presents several challenges. It has been argued that, in some contexts, forms of collective tenure such as a Community Land Trust may help to overcome some of these problems. This paper analyses one attempt to legalise informal tenure arrangements, minimise relocation and prevent gentrification by introducing collective titling in an informal settlement in Nairobi. The paper demonstrates how attempts to build consensus on the most appropriate tenure system were deeply embedded in local conflicts between existing structure-owners (owners of shacks/buildings on land which is not theirs) and tenants. The state was unable to carry out the land reforms it had proposed – to protect the land user rights of all residents – because they implied a redistribution that was resisted by local elite actors. This paper argues that tenure reforms are shaped by context-specific power relations; in this case the process was characterised by the implementers' need to maintain fragile agreements with local elites in order to avoid conflict. Tenure reforms are based on different ideas of whose rights should be recognised and competing claims are both negotiated through and shaped by the implementation process. Tenure reforms for contested land in informal settlements not only require technical mechanisms to prevent gentrification and displacement, but must reflect a serious consideration of local power relations and the capacity of the state to deal with conflicts arising from redistributive plans.